Plasma profile of hormones and energy metabolites during periparturient period in low and high producing Karan Fries (Holstein Friesian × Tharparkar) cows during different seasons - VAIDYA, MANGESH M; SINGH, SOHAN VIR; BEENAM, BEENAM; UPADHYAY, RAMESH C (The Indian Journal of Animal Sciences, 2015)
In order to find out the hormonal and metabolic profile during summer and winter season, five each of periparturient high and low yielding Karan Fries cows were selected from Livestock Research Centre (LRC) of ICAR-NDRI, Karnal. Blood samples were collected from both the group of animals on days (-45, -30, -15) of prepartum, 0 (expected day of calving) and on 15th, 30th and 45th day of postpartum during both the seasons. Plasma was separated by centrifuging the blood samples in the refrigerated centrifuge for energy metabolites and hormones. The plasma glucose levels were significantly lower on 0 day and remains lower upto 45th day of postpartum in both the groups and seasons compared to prepartum period (45 days). The plasma NEFA levels in high yielder group and during summer were higher on 15th day of postpartum compared to low yielders and during winter respectively. The plasma cortisol levels were significantly higher on the day of calving in high yielding group of Karan Fries cows compared to low yielding group animals . Plasma cortisol levels were significantly higher on the day of calving and remain higher during postpartum period (upto 45 days) in both groups and seasons compared to prepartum period. On the day of calving, plasma insulin, T3, T4 and leptin levels were significantly lower in high yielding group compared to low yielding group during both the seasons. The results of the present study clearly indicate more fluctuations in different stress markers in high yielding group compared to low yielding group during summer season. Although, both the groups of crossbred cows required protection during extreme climatic conditions, but high yielders group will require extra protection during the climate change scenario in future. Therefore, special care needs to be given to manage the high yielding animals during periparturient period to improve/maintain the productivity.